Attitudes of Malaysian Teachers Toward a Performance-Appraisal System - Rahman, Shukran Abdul (Blackwell Publishing, 2006)
This study investigated the attitudes of teachers of different ethnic origins in Malaysia toward an outcome-oriented performance appraisal, the New Performance Appraisal System (NPAS). It also investigated the relationship between teachers' attitudes toward the system and their job satisfaction and professional commitment. Teachers of the major ethnic origins in Malaysia - Malays, Chinese, and Indians - were selected randomly from 6 public high schools in the state of Kedah. The study found that teachers of all ethnic origins reported less favorable attitudes toward the NPAS, and that their cultural dimension had no bearing on attitudes toward the NPAS. Teachers who received appropriate explanation and supervision of their performance, despite low performance-appraisal results, reported high levels of job satisfaction and professional commitment